Hashtag commerce: "Order by Tweet". Issue 1 (May 2019) - O'Leary, Daniel E
Recently, American Express introduced the use of "hashtag" commerce for their cardholders into Twitter using the notion of "Order by Tweet": transactions were initiated and confirmed within Twitter using unique hashtags. Shortly after American Express, Amazon.com initiated their version of social commerce with #AmazonCart, where product requests were sent from Twitter to user's carts in Amazon. These implementations were some of the first examples of social commerce actually executing transactions in the context of a social media platform. After American Express and Amazon, Domino's Pizza introduced "Order by Tweet" into fast food ordering and payment. This case examines the processes that have been used as part of the processing of those transactions and allows analysis of some of the strengths and limitations of the resulting approaches.